Italian validation of the workplace ostracism scale (WOS) - Colledani, Daiana; De Carlo, Alessandro; Falvo, Rossella; Capozza, Dora (Frontiers in Psychology, 2025)
IntroductionThe aim of this study was to validate the Italian version of the workplace ostracism scale (WOS), developed by Ferris and colleagues. Workplace ostracism (WO)—the perception of being ignored or excluded by colleagues or supervisors—is a painful experience that negatively impacts employees and the whole organization. We tested the unidimensional structure of the Italian WOS, its independence of social desirability issues, and invariance across genders and ages. We also tested the nomological validity of the WOS by considering ostracism as a job demand and including it in the job demands-resources (JD-R) theory.MethodA sample of Italian employees (N = 653), working for different organizations in several Italian regions, completed an online questionnaire. Data were analyzed using exploratory and confirmatory factor analyses. Network analysis was applied to test the nomological validity of the scale.ResultsFindings confirmed the unifactor structure of the Italian WOS and its invariance. Social desirability only absorbed a limited portion of variance of ostracism items. Data also supported the nomological validity of the WOS, that is, the expected association of ostracism with basic need frustration, lower work engagement, altruism, and performance.DiscussionIn the discussion, we clarified the advantages of conceiving ostracism as a job demand and using network analysis to verify the JD-R theory. Practical implications of findings in order to contain workplace ostracism were commented.